Strategi Pengembangan Berbasis Inovasi Nilai Produk Seafood Crispy Menggunakan Quality Fuction Deployment - Siti Salama Amar (Universitas Medan Area, 2019)
This research was conducted to design a business strategy of crispy seafood SMEs, especially in Pamekasan Madura, in order to improve product competitiveness. The product development strategy was analyzed using Quality Function Deployment (QFD) which was subsequently integrated with Blue Ocean Strategy (BOS) in a four-step analysis framework (ERRC Grip), in order to obtain highly competitive products and get out of red ocean competition. This study collected data with interview techniques on crispy seafood IKM and questionnaires involving 180 respondents. From the respondents' evaluation of 17 indicators of customer satisfaction, only 7 indicators exceeded customer expectations. Through the planning matrix, indicators of satisfaction (customer requirements) are identified into 9 technical requirements (responses) and result in an increase in product quality that must be considered and prioritized crispy seafood IKM outlined in the HoQ Matrix. The four biggest priorities for increasing the competitiveness of crispy sea seafood products are market reach, packaging design, quality of supporting materials and prices. All response techniques then analyzed using ERRC Grip, which can be used as a guideline for SMEs in conducting business and out of the competition for the red ocean to blue ocean